2003
DOI: 10.1001/archpsyc.60.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Its Influence on Reproductive Endocrine and Menstrual Cycle Markers Associated With Perimenopause

Abstract: A lifetime history of major depression may be associated with an early decline in ovarian function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
129
0
5

Year Published

2004
2004
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 208 publications
(146 citation statements)
references
References 28 publications
5
129
0
5
Order By: Relevance
“…However, the most recent longitudinal, community-based studies suggest perimenopausal transition rather than menopause itself to be the point of increased vulnerability for depressive episodes [52][53][54][55][56][57] even in the absence of a history of depression [58,59] or in asymptomatic women [59]. Vasomotor symptoms (directly attributable to menopausal estrogen withdrawal) have been observed to increase the risk of depressive symptoms in perimenopausal women but not in pre-or postmenopausal women in primary care [60] and also in a population sample, but they were not shown to be independently associated with diagnosed depressive disorder in population [57,58].…”
Section: Menopausementioning
confidence: 99%
“…However, the most recent longitudinal, community-based studies suggest perimenopausal transition rather than menopause itself to be the point of increased vulnerability for depressive episodes [52][53][54][55][56][57] even in the absence of a history of depression [58,59] or in asymptomatic women [59]. Vasomotor symptoms (directly attributable to menopausal estrogen withdrawal) have been observed to increase the risk of depressive symptoms in perimenopausal women but not in pre-or postmenopausal women in primary care [60] and also in a population sample, but they were not shown to be independently associated with diagnosed depressive disorder in population [57,58].…”
Section: Menopausementioning
confidence: 99%
“…The study concluded that depression was associated with early onset of perimenopause, notably the depression suffers had higher follicle-stimulating hormone and leuteinizing hormone levels and lower estradiol levels. 62 A gynecological history of nulliparity, early menarche, tobacco smoking, or unilateral oophorectomy are also predisposing conditions for a woman to enter early perimenopause.…”
Section: Perimenopausementioning
confidence: 99%
“…In this case, authors concluded that a lifetime history of major depression may be associated with an early decline of ovarian function, a situation that characterizes menopause transition (Harlow et al, 2003). On the other hand, in a similar study, women with no history of depression, had increased levels of FSH and LH and increased variability of estradiol that were significantly associated with depressive symptoms (Freeman et al, 2006).…”
Section: Monoamines and Depressionmentioning
confidence: 80%
“…Other studies that have shown the participation of estrogens in the etiology of depression are the following: a prospective study showed that women with a lifetime history of depression had high levels of follicle-stimulating and luteinizing hormones levels, but low estradiol concentrations (Harlow et al, 2003). In this case, authors concluded that a lifetime history of major depression may be associated with an early decline of ovarian function, a situation that characterizes menopause transition (Harlow et al, 2003).…”
Section: Monoamines and Depressionmentioning
confidence: 95%